The king's foot of patient-reported outcomes: current practices and new developments for the measurement of change. - Swartz RJ; Schwartz C; Basch E; Cai L; Fairclough DL; McLeod L; Mendoza TR; Rapkin B; Swartz, Richard J; Schwartz, Carolyn; Basch, Ethan; Cai, Li; et al. (Quality of Life Research, 2011)
Purpose: Assessing change remains a challenge in patient-reported outcomes. In June 2009, a group of psychometricians, biostatisticians, and behavioral researchers from other disciplines convened as a Longitudinal Analysis of Patient-Reported Outcomes Working group as part of the Statistical and Applied Mathematical Sciences Institute Summer Psychometric program to discuss the complex issues that arise when conceptualizing and operationalizing "change" in patient-reported outcome (PRO) measures and related constructs. This white paper summarizes these issues and provides recommendations and possible paths for dealing with the complexities of measuring change.Methods/results: This article presents and discusses issues associated with: (1) conceptualizing and operationalizing change in PRO measures; (2) modeling change using state-of-the-art statistical methods; (3) impediments to detecting true change; (4) new developments to deal with these challenges; and (5) important gaps that are fertile ground for future research.Conclusions: There was a consensus that important research still needs to be performed in order develop and refine high-quality PRO measures and statistical methods to analyze and model change in PRO constructs.